Macroscopic electric field inside water-filled biological nanopores. Issue 13 (2nd March 2016) - Gutiérrez, Silvia Acosta; Bodrenko, Igor; Scorciapino, Mariano Andrea; Ceccarelli, Matteo
Abstract : We used water as a natural probe to evaluate the macroscopic electric field inside nanometric water-filled channels. Abstract : Multi-drug resistance bacteria are a challenging problem of contemporary medicine. This is particularly critical for Gram-negative bacteria, where antibiotics are hindered by the outer membrane to reach internal targets. Here more polar antibiotics make use of nanometric water-filled channels to permeate inside. We present in this work a computational all-atom approach, using water as a probe, for the calculation of the macroscopic electric field inside water-filled channels. The method allows one to compare not only different systems but also the same system under different conditions, such as pH and ion concentration. This provides a detailed picture of electrostatics in biological nanopores shedding more light on how the charged residues of proteins determine the electric field inside, and also how medium can tune it. These details are central to unveil the filtering mechanism behind the permeation of small polar molecules through nanometric water-filled channels.